La actividad sexual reciente de las mujeres en México entre 1987 y 2018. Un análisis a partir de encuestas demográficas - Gayet, Cecilia; Szasz, Ivonne (El Colegio de México A.C., 2024)
The article aims to examine the sexual activity of adult women in Mexico (during the previous month before the interview), investigating the variations based on age, education, locality size, union status, intention to have a child, and whether the women have young children, comparing two surveys over time (Enfes 1987 and Enadid 2018). Women in 2018 who were in a union were studied to determine the relationship between sexual activity and the age, type (marriage versus consensual union), and order of union. Compared to 1987, the results show higher rates of reporting sexual intercourse in 2018, especially among older and single women. The higher the level of schooling, the higher the proportion of women who reported having had sexual intercourse. Intention to have a child increases the odds ratio of having sex, and being pregnant or having young children decreases. Age and length of union decreased recent sexual activity only among women older than 45 years.